Experimental study of high energy electron interactions in a superconducting aluminum alloy resonant bar - Barucci, M; Bassan, M; Buonomo, B; Cavallari, G; Coccia, E; D'Antonio, S; Fafone, V; Ligi, C; Lolli, L; Marini, A; Mazzitelli, G; Modestino, G; et al. (2009)
Peak amplitude measurements of the fundamental mode of oscillation of a suspended aluminum alloy bar hit by an electron beam show that the amplitude is enhanced by a factor ~3.5 when the material is in the superconducting state. This result is consistent with the cosmic ray observations made by the resonant gravitational wave detector NAUTILUS, made of the same alloy, when operated in the superconducting state. A comparison of the experimental data with the predictions of the model describing the underlying physical process is also presented.